The Use of Dictogloss Technique to Improve Students’ Writing Ability - Dian Mega Putri; Endang Komariah; Arifin Syamaun (Universitas Syiah Kuala, 2021)
This research is a library study which aims at analyzing how Dictogloss technique improves students writing ability based on the literature analysis. This research focused on Nunan’s theory with his 4 steps of dictogloss, which are preparation, dictation, reconstruction, analysis and correction. The data were collected using investigation technique of discourses from textbooks, articles, journals, papers and other relevant data sources. This research was re-analyzed the relationship between all data and raw data previously obtained in data collection technique. Such results were reviewed by the author look for similarities or association between one source and another source, as well as to search for strengths and limitations from both sources. The result of the analysis showed that the use of dictogloss technique could improve students writing ability in terms of all aspects of writing based on four steps of dictogloss procedure. The reason is in every step of dictogloss make students work together in a group, and then in the step of dictogloss students can ask a teacher what they do not understand, and also students are involved in a restructure stage and analysis correction stage. It makes students easier in writing English and improves the students writing ability. It can be concluded that this technique can be used to improve students writing ability.